FAKTOR-FAKTOR YANG MEMPENGARUHI KEMENANGAN TALIBAN DI AFGHANISTAN - Brahma Syafrudin Putra (2022)
After the September 11, 2001 WTC Tragedy, the Taliban came under the spotlight of the United States government because they had allied themselves with Al-Qaeda. The Taliban leadership protected Osama Bin Laden from being targeted by the United States government so that the United States military was deployed to Afghanistan to capture the Taliban leader and to destroy his network. However the Talibans are not so easily pushed over, even by the strongest military in the world, The United States. For almost 20 years, the Talibans were able to hold the United States' military might, evem pushing them back from winning the state of Afghanistam, until in 2021 the Taliban have succeeded in occupying and taking over the presidential palace after the President of Afghanistan fled and managed to get the Americans to decide to withdraw all of their troops from the city of Kabul in Afghanistan. This study has the purpose to find out the main factors that lead to Taliban's victory over the U.S, which is significant for the Middle-east region and even the world. This study is expected to give out what are the causes behind the Taliban's strenght througout the war period. In this study, the author uses a qualitative, describtive method in order to explain the issue thoroughly. The main data source will be collected through interview and literature studies. This study will answer the question what are the factors that led to Taliban's victory in Afghanistan? These factors might not be able to ba labeled as the main factors just yet, because as of now, most of the source of this study are gathered through Western Medias. There are not a lot of sources from the Taliban just yet.